Teaching at primary healthcare services within the Brazilian national health system (SUS) in Brazilian healthcare professionals' training - Ramona Fernanda Ceriotti Toassi; Alexandre Baumgarten; Cristine Maria Warmling; Eloá Rossoni; Arisson Rocha da Rosa; Sonia Maria Blauth Slavutzky (Faculdade de Medicina de Botucatu (Unesp), 2013)
The aim of this study was to analyze the role of teaching at primary healthcare services within the Brazilian National Health System (SUS) in dentists' training, at a public university in the south of Brazil. A qualitative methodological approach (case study) was used. Interviews were conducted with 12 dentistry students, six dentists who were preceptors working in public primary healthcare services and three teachers connected with this curricular training. Our findings showed that the curricular training in SUS primary healthcare services had an impact on the dentists' education through establishment of bonds, autonomy in problem-solving and multiprofessional teamwork. It was seen that they learned about how healthcare services function, about healthcare and about development of cultural competence. There is a need to maintain constant questioning regarding these practices, and to ensure the presence of infrastructure and qualified professionals for teaching at these services.